2005
DOI: 10.1073/pnas.0502402102
|View full text |Cite
|
Sign up to set email alerts
|

Modifying specific cysteines of the electrophile-sensing human Keap1 protein is insufficient to disrupt binding to the Nrf2 domain Neh2

Abstract: The risks of cancer and other degenerative diseases caused by reactive oxygen species and electrophiles can be reduced by the up-regulation of detoxifying enzymes. A major mechanism whereby these protective enzymes are induced occurs through activation of the antioxidant response element (ARE) by the oxidative-stress sensor protein Kelch-like ECH-associated protein 1 (Keap1) and the transcription factor NF-E2-related factor 2 (Nrf2). Under basal conditions, Keap1 sequesters Nrf2 in the cytoplasm by binding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
377
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 418 publications
(407 citation statements)
references
References 34 publications
19
377
1
Order By: Relevance
“…Human Keap1 is structurally organized into five major domains: the N-terminal domain (amino acids 1-60); the "Broad complex, tramtrack and bric-a-brac" BTB domain (amino acids 61-179); the central intervening IVR domain (amino acids 180-314); a double glycine-rich domain comprising six Kelch repeat motifs (amino acids 315-359, 361-410, 412-457, 459-504, 506-551, and 553-598); and a C-terminal domain (amino acids 599-624). The BTB and IVR domains are required for the redox-and electrophile-sensitive regulation of Nrf2 through a series of reactive cysteines [113][114][115]. Human Keap1 has 27 cysteine residues (while rodent Keap1 has 25), nine of which are predicted to be particularly reactive due to their location adjacent to basic amino acids.…”
Section: Acrolein As An Inducer Of the Keap1-nrf2-dependent Are/epre mentioning
confidence: 99%
See 2 more Smart Citations
“…Human Keap1 is structurally organized into five major domains: the N-terminal domain (amino acids 1-60); the "Broad complex, tramtrack and bric-a-brac" BTB domain (amino acids 61-179); the central intervening IVR domain (amino acids 180-314); a double glycine-rich domain comprising six Kelch repeat motifs (amino acids 315-359, 361-410, 412-457, 459-504, 506-551, and 553-598); and a C-terminal domain (amino acids 599-624). The BTB and IVR domains are required for the redox-and electrophile-sensitive regulation of Nrf2 through a series of reactive cysteines [113][114][115]. Human Keap1 has 27 cysteine residues (while rodent Keap1 has 25), nine of which are predicted to be particularly reactive due to their location adjacent to basic amino acids.…”
Section: Acrolein As An Inducer Of the Keap1-nrf2-dependent Are/epre mentioning
confidence: 99%
“…It appeared that the reactivities of the cysteines in human Keap1 are different from the corresponding cysteines in mouse Keap1 [112][113][114][115]117]. Despite some uncertainty regarding the exact order of the reactivity of the cysteine residues towards different electrophiles, Cys-151 (located in the BTB domain) was identified as the most reactive nucleophilic site in human Keap1 [113,117]. It is conceivable that multiple cysteines in Keap1 can be modified by different inducers and it is likely that sites of sulfhydryl modification may vary among the different chemical compound classes and across species [118].…”
Section: Acrolein As An Inducer Of the Keap1-nrf2-dependent Are/epre mentioning
confidence: 99%
See 1 more Smart Citation
“…In their studies of murine Keap1, Dinkova-Kostova et al [2] used MALDI-TOF to identify modified peptides in a tryptic digest, but LC-MS/MS was used to confirm the sequence and to determine the site of modification in only two of the four modified peptides. Our previous study [30] in which human Keap1 modifications were mapped indicated that C151, C288, and C297 are the most reactive residues toward iodoacetyl-N-biotinyl hexylene diamine. A similar study was reported by Hong et al [13], but their data suggested that C169, C241, and C288 but not C151 were reactive toward human Keap1.…”
Section: Modification Sites Of Human Keap1 By Electrophilesmentioning
confidence: 99%
“…The details of the cloning, expression, and purification of human Keap1 are described elsewhere [30]. BMCC was purchased from Pierce (Rockford, IL), and trypsin was purchased from Promega (Madison, WI).…”
Section: Materials and Reagentsmentioning
confidence: 99%